2005
DOI: 10.1524/zpch.219.7.979.67092
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Correlations for the Oxidation of CO over Polycrystalline RuO2 Powder Derived from Steady-State and Transient Kinetic Experiments

Abstract: Ruthenium Dioxide (RuO 2 ) / CO Oxidation / Kinetics / Temperature-Programmed Reduction (TPR) / Shell-Core ModelThe oxidation of carbon monoxide was studied at atmospheric pressure in a plug-flow reactor over polycrystalline ruthenium dioxide powder in the temperature range from 363 to 453 K as a function of the pretreatment. Calcining RuO 2 in flowing oxygen resulted in purified bulk RuO 2 , whereas reduction in hydrogen led to bulk Ru metal, which was partially oxidized again in flowing oxygen at increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 20 publications
(43 reference statements)
6
59
0
1
Order By: Relevance
“…It was evidenced by the evolution of the Ru 3d and O 1s spectra, which was terminated at the formation of 'surface oxide'. The CO 2 yield grew steadily showing stable activity at constant temperature until levelling off at around 500 K and declining slowly above 550 K. This result is qualitative agreement with the results with powdered Ru catalyst which demonstrate that an ultra-thin oxide layer covering the metallic Ru core is the active state in CO oxidation at temperatures below 500 K [33].…”
Section: Figuresupporting
confidence: 89%
See 1 more Smart Citation
“…It was evidenced by the evolution of the Ru 3d and O 1s spectra, which was terminated at the formation of 'surface oxide'. The CO 2 yield grew steadily showing stable activity at constant temperature until levelling off at around 500 K and declining slowly above 550 K. This result is qualitative agreement with the results with powdered Ru catalyst which demonstrate that an ultra-thin oxide layer covering the metallic Ru core is the active state in CO oxidation at temperatures below 500 K [33].…”
Section: Figuresupporting
confidence: 89%
“…The longrange ordering of the RuO 2 (110) surface is not prerequisite for catalytic function but was instrument to unravel and theoretically understand mechanisms of CO oxidation at the atomic level. As noted above, very recent study of the CO oxidation on polycrystalline powdered Ru catalyst in the temperature range 363-453 K showed that under dynamic catalytic conditions the active state are the ultra-thin Ru oxide films, whereas fully oxidized RuO 2 particles, formed at higher temperature, exhibit lower activity [33]. This deactivation is tentatively attributed to roughening and formation of inactive RuO 2 facets.…”
Section: Discussionmentioning
confidence: 82%
“…The occurrence of this reconstructed RuO 2 (100)-c(2 × 2) surface is nicely supported by our experiments: First, the irregular octagonal cross section habit of the calcined RuO 2 crystals in contrast to the obelisk-like habit shown in the literature [24] points to an equilibration of the (110) and (100) surface energies. This would be the case for a RuO 2 (100)-c(2 × 2) microfacetted (110) surface.…”
Section: Ruo 2 As Bulk Phasesupporting
confidence: 87%
“…The same argument holds for the immediate activity of polycrystalline pre-calcined RuO 2 in Narkhede et al [24] because they used a low precalcination temperature of 573 K. Since our very long induction times are not reported in the literature we will discuss them in the context of deactivation.…”
Section: Ruo 2 As Bulk Phasementioning
confidence: 52%
See 1 more Smart Citation